Ill-posed equations with transformed argument - Simone Gramsch; Eberhard Schock (Abstract and Applied Analysis)
We discuss the operator transforming the argument of a function in the L2-setting. Here this operator is unbounded and closed. For the approximate solution of ill-posed equations with closed operators, we present a new view on the Tikhonov regularization.